Penicibrocazines A–E, Five New Sulfide Diketopiperazines from the Marine-Derived Endophytic Fungus Penicillium brocae - Meng, Ling-Hong (Mar Drugs, 2015)
Five new sulfide diketopiperazine derivatives, namely, penicibrocazines A–E (1–5), along with a known congener (6), were isolated and identified from the culture extract of Penicillium brocae MA-231, an endophytic fungus obtained from the fresh tissue of the marine mangrove plant Avicennia marina. The structures of these compounds were elucidated by detailed interpretation of NMR and mass spectroscopic data and the structures of compounds 1 and 3 were confirmed by single-crystal X-ray diffraction analysis. All these compounds were examined for cytotoxic and antimicrobial activities. Compounds 2–6 exhibited antimicrobial activity against some of the tested strains with MIC values ranging from 0.25 to 64 μg/mL.